Effect of anthraquinone-2, 6-disulfonate on the photolysis of 2, 4, 4′-tribromophenylphenyl ether. Issue 6 (24th April 2017) - Yuan, Wei; Lu, Guining; Xie, Yingying; Huang, Kaibo; Wang, Rui; Yin, Hua; Dang, Zhi
Abstract : AQDS can produce reactive oxygen species ( 1 O2, ˙OH) to promote the degradation of BDE-28, and can also bind to BDE-28 molecules to inhibit the degradation of BDE-28. Abstract : In this study, we have investigated the photolysis of 2, 4, 4′-tribromophenylphenyl ether (BDE-28) in Triton X-100 (TX-100) solutions, and discussed the effect of anthraquinone-2, 6-disulfonate (AQDS) on the photolysis of BDE-28. The effect of TX-100 on the photolysis of BDE-28 was mainly related to the concentration of TX-100. The fastest photolysis of BDE-28 was at 500 mg L −1 of the TX-100 solution, and the corresponding photolysis rate constant was 0.12 min −1 . The direct photolysis rate of BDE-28 decreased from 0.17 min −1 to 0.08 min −1 and 0.12 min −1 when NaN3 and isopropanol were added, respectively. The effect of AQDS on the photolysis of BDE-28 was also mainly related to the concentration of AQDS. When the concentration of AQDS was 0.6 μM, it has a slight influence in promoting the photodegradation of BDE-28; as the AQDS concentrations increased, the suppressing effect was more obvious. AQDS can inhibit the photolysis of BDE-28. Photolysis kinetics and quenching reactions illustrated that BDE-28 can produce a photosensitization reaction in TX-100 solutions, and the effects of AQDS on the photolysis of BDE-28 were mainly dominated by inhibition. In addition to its light shielding effect, AQDS can also combine with BDE-28 and anti-oxidation to inhibit the photolysis of BDE-28. We found that the degradation pathway of BDE-28 was mainly based on de-bromination, and the ions at para positions were preferentially debrominated.